2021
DOI: 10.1002/ehf2.13656
|View full text |Cite
|
Sign up to set email alerts
|

Relation of left atrial function with exercise capacity and muscle endurance in patients with heart failure

Abstract: Aims Both left atrial strain (LAS) and skeletal muscle endurance demonstrate a linear relationship to peak VO 2 . Less is known about the relationship between central (cardiac) and peripheral (muscle endurance) limitations of exercise capacity in patients with heart failure (HF). We investigated this relationship using novel cardiac markers such as LAS and left atrial emptying fraction (LAEF). Methods and resultsWe analysed echocardiographic measurements, cardiopulmonary exercise testing (CPET), and isokinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Forty-one studies [14-53] published from 2008 to 2022 were investigated, including 27 case-control studies, 12 prospective cohort studies, and 2 retrospective cohort studies. Table 1 shows the baseline features of the selected research.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty-one studies [14-53] published from 2008 to 2022 were investigated, including 27 case-control studies, 12 prospective cohort studies, and 2 retrospective cohort studies. Table 1 shows the baseline features of the selected research.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-one studies[1434] explored the differences in LV GLS values between HFpEF patients (n=1431) and healthy controls (n=864), with a mean LV GLS of - 16.07%±3.32% vs. -19.54%± 2.57% (Fig 2A). Moreover, 16 studies[14–18,21,26,30,33– 40] examined discrepancies in LV GLS values between HFpEF patients (n=2,234) and HFrEF patients (n=3,355), with an average LV GLS of -16.42%±3.56% vs. -9.3%±3.48% (Fig 2B).…”
Section: Resultsmentioning
confidence: 99%
“…Von Roeder et al ( 39 ) and Kusunose et al ( 40 ) found that a decrease in METS was associated with left ventricular diastolic dysfunction, as well as the size and function of the left atrium. In addition, the LASr can explain the relationship between cardiac and peripheral exercise capacity reduction ( 41 ), whereas the association between METS and left ventricular systolic function is relatively weak. Patel et al ( 42 ) showed that diminished exercise capacity was associated with inadequate biatrial function, insufficient left atrial functional reserve, and left ventricular diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%